Investigation of the Phase Transition and Absorption Properties of Liquid Crystal Hexylcyanobiphenyl/Octylcyanobiphenyl Mixtures - Okumus, Mustafa; Özgan, Sükrü (Asian Journal of Chemistry, 2013)
The hexylcyanobiphenyl (6CB) and octylcyanobiphenyl (8CB) mixtures have been investigated by means of differential scanning calorimeter and ultraviolet. Differential scanning calorimeter results indicate clearly the existence of four phase transitions in the 6CB/8CB mixtures. The phase diagram of mixture was obtained from differential scanning calorimeter and theoretical calculations. The experimental phase diagram is approximately similar to the calculated phase diagram. The phase transition temperatures of the 6CB/8CB mixtures rise with the heating rate between 2 ºC/min and 10 ºC/min. The activation energies were calculated for the phase transitions of 50 % 6CB and 50 % 8CB liquid crystal mixtures. UV experiments were carried out to characterize the absorptivity constants of liquid crystal and their mixtures. The molar absorptivity and maximum absorption wavelengths were measured in chloroform solution by UV spectrophotometry. The maximum absorption wavelength of the 6CB/8CB mixtures increases with decreasing percent weight of 8CB in 6CB, a result associated with the different lengths of the alkyl chain.